2017
DOI: 10.1038/ncomms15938
|View full text |Cite|
|
Sign up to set email alerts
|

High performance platinum single atom electrocatalyst for oxygen reduction reaction

Abstract: For the large-scale sustainable implementation of polymer electrolyte membrane fuel cells in vehicles, high-performance electrocatalysts with low platinum consumption are desirable for use as cathode material during the oxygen reduction reaction in fuel cells. Here we report a carbon black-supported cost-effective, efficient and durable platinum single-atom electrocatalyst with carbon monoxide/methanol tolerance for the cathodic oxygen reduction reaction. The acidic single-cell with such a catalyst as cathode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
490
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 638 publications
(526 citation statements)
references
References 54 publications
14
490
1
3
Order By: Relevance
“…[28,54,121] However,s urpassing the efficiencyo fP t/C is challenging since the reaction proceeds by a2e À pathway and produces less electricity than the alternative 4e À pathway.On the other hand, this presents an efficient route for the H 2 O 2 synthesis,i nw hich case higher selectivity is expected upon complete elimination of NPs and clusters.T he improved performance of aPt 1 /TiC catalyst than Pt 1 /TiN indicated that the support can strongly influence the performance. [28,54,121] However,s urpassing the efficiencyo fP t/C is challenging since the reaction proceeds by a2e À pathway and produces less electricity than the alternative 4e À pathway.On the other hand, this presents an efficient route for the H 2 O 2 synthesis,i nw hich case higher selectivity is expected upon complete elimination of NPs and clusters.T he improved performance of aPt 1 /TiC catalyst than Pt 1 /TiN indicated that the support can strongly influence the performance.…”
Section: Electrocatalysismentioning
confidence: 99%
“…[28,54,121] However,s urpassing the efficiencyo fP t/C is challenging since the reaction proceeds by a2e À pathway and produces less electricity than the alternative 4e À pathway.On the other hand, this presents an efficient route for the H 2 O 2 synthesis,i nw hich case higher selectivity is expected upon complete elimination of NPs and clusters.T he improved performance of aPt 1 /TiC catalyst than Pt 1 /TiN indicated that the support can strongly influence the performance. [28,54,121] However,s urpassing the efficiencyo fP t/C is challenging since the reaction proceeds by a2e À pathway and produces less electricity than the alternative 4e À pathway.On the other hand, this presents an efficient route for the H 2 O 2 synthesis,i nw hich case higher selectivity is expected upon complete elimination of NPs and clusters.T he improved performance of aPt 1 /TiC catalyst than Pt 1 /TiN indicated that the support can strongly influence the performance.…”
Section: Electrocatalysismentioning
confidence: 99%
“…8 To further investigate the electronic structure and coordination environments of single Pt atoms in Pt-GDY1 and Pt-GDY2, the Pt L 3 -edge X-ray absorption near edge structure (XANES) and extended X-ray fine structure (EXAFS) were studied. [28] Furthermore,t he L 3 -edge white-line (WL) intensities increase in an order of Pt foil < Pt-GDY1 < Pt-GDY2 (inset in Figure 3c). [28] Furthermore,t he L 3 -edge white-line (WL) intensities increase in an order of Pt foil < Pt-GDY1 < Pt-GDY2 (inset in Figure 3c).…”
mentioning
confidence: 99%
“…[12,[16][17][18][19][20][21][22][23] Downsizing catalyst nanoparticles to single atoms could be desirable to enhance utilization efficiency of noble metal atoms. [24] Recently, single-atom catalysts (SACs) have been attracted increasingly as their high activity for a wide variety of chemical reactions, [24][25][26][27][28] such as oxygen reduction reaction (ORR) [27] and hydrogen evolution reaction (HER). [24] However, it is still a great challenge to fabricate stable SACs as single atoms can easily migrate and agglomerate during preparation and catalytic process.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Recently, single-atom catalysts (SACs) have been attracted increasingly as their high activity for a wide variety of chemical reactions, [24][25][26][27][28] such as oxygen reduction reaction (ORR) [27] and hydrogen evolution reaction (HER). [24] However, it is still a great challenge to fabricate stable SACs as single atoms can easily migrate and agglomerate during preparation and catalytic process. [29] An appropriate substrate that interacts with single atom is possible to enhance the stability of SACs without severely impairing their activity and selectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation